Vitamin C Intakeand Risk Factors for Knee Osteoarthritis - Nadia Ayu Destiani; Siti Nur Fatimah; Sumartini Dewi (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Knee osteoarthritis (OA) is a degenerative disease of the knee joints characterized by progressive softening and disintegration of articular cartilage. In OA, which is influenced by several risk factors, free radicals are increased by local ischemia in the cartilage. As an exogenous antioxidant, vitamin C also plays an important role in collagen and glycosaminoglycan synthesis. This study was carried out to identify vitamin C intake as well as risk factors in knee OA. Methods: The study population was determined by non-probability sampling with convenient approach to knee OA patients at the Rheumatology Outpatient Clinic of Dr. Hasan Sadikin General Hospital in October–November 2013. Data were obtained through questionnaire interview about risk factors, severity index of OA and vitamin C intake profile. Data presentation was conducted by descriptive method.Results: There were 47 patients diagnosed with knee OA in the Rheumatology Outpatient Clinic. The result showed that 7 patients (14.9%) had low vitamin C intake for the last 3 months. There were 30 patients with family history of OA (63.8%). Thirty two patients (68.1%) were passive smokers, 44 patients (93.6%) had history of repeated use of knee joints and majority of respondents had obesity. Conclusions: Most of the subjects have sufficient vitamin C intake and more than half have risk factors that may contribute to the incidence of knee OA. DOI: 10.15850/amj.v4n2.1067